HOW INDUSTRY PLAYERS PERCEIVED PAYMENT ISSUES IN INDUSTRIALISED BUILDING SYSTEM (IBS) HOUSING PROJECTS? - Ahmad, Abd Jalil; Mastura, Jaafar; Azlan Raofuddin, Nuruddin; Md Azree, Othuman Mydin (Construction Industry Development Board, 2017)
Housing projects have become one of the significant contributors to our national gross domestic product. However, since 1990s housing sector was known for its poor performance, heavily depending on foreign labors, increasing cost and cannot cater to the demand. Malaysian National Housing Policy 2012 has focused on the implementation of industrialised building system (IBS) to transform the housing industry by improving its quality, more economical, speed to construct and less dependency on foreign labors. Despite of these advantages and great efforts from the government, recent studies show that the IBS adoption is still far behind the target. Among the identified and significant challenges that discourage housing projects from adopting IBS is the payment system which is closely associated with procurement adopted. Adopting traditional procurement system which is suited for conventional construction method has been create problems to the industry players. Due to this, many developers either neglect to adopt IBS or if they adopt it, the related parties have to face payment difficulties. This paper explores payment challenges in IBS housing projects, and ways to overcome them. The findings can be used for the industry to justify on the need for a better procurement system for IBS project.